Selection Factors of Islamic Banking between Banks Islam Malaysia Berhad and Conventional Banks in Sabah: What do Their Customers Say? - Md. Kamdari, N. A.; Yusoff, R.; Abd. Rahim, D. A. (Universiti Sains Islam Malaysia, 2024)
This study attempted to investigate the selection factors of Islamic banking customers and depositors based on data collected from various groups of public servants who are customers and depositors of a fullfledget Islamic bank in Sabah, namely, Bank Islam Malaysia Berhad (BIMB) and conventional banks offering Islamic windows. Using a sample of 500 respondents, this paper explored the main selection factors of the depositors and customers of BIMB and Islamic banking scheme of conventional banks. Based on the main interpretation of the varimax rotated matrix first factors, the results from the customers and depositors of BIMB delineated a cluster of relationship for 'location' (X3), income of depositor(X5), customers services quality (X4), and product price (X6). Whereas for the conventional banks offering Islamic windows the factors are 'location' (X3), income of depositor(X5), customers service quality (X4), Islamic reputation and image (Y1).